2018
DOI: 10.1002/jbmr.3480
|View full text |Cite|
|
Sign up to set email alerts
|

Hypocitraturia Is an Untoward Side Effect of Synthetic Human Parathyroid Hormone (hPTH) 1-34 Therapy in Hypoparathyroidism That May Increase Renal Morbidity

Abstract: Subcutaneous human parathyroid hormone (hPTH) therapy can effectively manage hypocalcemia in hypoparathyroidism, with varying effects on hypercalciuria. However, little is known about its ability to decrease the renal comorbidities of hypoparathyroidism: nephrocalcinosis (NC), nephrolithiasis (NL), and renal insufficiency. Urinary citrate (Ucit) promotes the solubility of urinary calcium (UCa); hypocitraturia is a risk factor for NC/NL. Twenty-four-hour UCa, Ucit, and UCa/Ucit were determined in 31 hypoparathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…A recent paper by Gafni and coworkers 57 seems to suggest that treatment with subcutaneous PTH 1-34 in patients with hypoparathyroidism may have untoward effects of hypocitraturia, thus increasing renal morbidity. No similar study has been carried out in the setting of osteoporosis; however, this possible biochemical abnormality should be better defined in patients receiving the hormone not as a substitution therapy.…”
Section: Side Effectsmentioning
confidence: 99%
“…A recent paper by Gafni and coworkers 57 seems to suggest that treatment with subcutaneous PTH 1-34 in patients with hypoparathyroidism may have untoward effects of hypocitraturia, thus increasing renal morbidity. No similar study has been carried out in the setting of osteoporosis; however, this possible biochemical abnormality should be better defined in patients receiving the hormone not as a substitution therapy.…”
Section: Side Effectsmentioning
confidence: 99%
“…This was a longitudinal open‐label, uncontrolled study of synthetic human PTH 1‐34 (hPTH) replacement therapy in 31 patients with hypoparathyroidism (25 women, six men), ages 16 to 60 years old. ( 27 ) Included patients had physician‐diagnosed hypoparathyroidism for at least 1 year, confirmed by an intact PTH <30 pg/mL with concomitant blood calcium below the normal range upon screening. The majority of patients ( 20 ) had postsurgical hypoparathyroidism; four had activating pathogenic variants of the calcium‐sensing receptor, two had 22q11.2 deletion syndrome, one had hypoparathyroidism‐deafness‐renal syndrome, and four had idiopathic/acquired autoimmune disease.…”
Section: Methodsmentioning
confidence: 99%
“…Winer et al showed that twice daily PTH (1‐34) kept a more stable metabolic level than the once‐daily dose (Winer, Sinaii, Peterson, Sainz, & Cutler, 2008). Overdosed PTH (1‐34) has the potential to bring hypocitraturia that is harmful to kidneys (Gafni et al, 2018). As for transplantation, allotransplantation was first used in postsurgical hypoparathyroidism but is still not popular enough considering the shortage of safe and functional cell or tissue resources (Agha et al, 2016; Khryshchanovich & Ghoussein, 2016; Tibell et al, 2001).…”
Section: Parathyroid‐related Diseases and Clinical Therapiesmentioning
confidence: 99%